STRUKTUR PENDAPATAN DAN STRUKTUR PENGELUARAN SERTA MEKANISME KOPING PETANI PEMILIK SEKALIGUS PENGGARAP DI KELURAHAN SETIANAGARA KECAMATAN CIBEUREUM KOTA TASIKMALAYA - Sudama, Farhan Shidiq; Noor, Trisna Insan (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Coping mechanism is a strategy made by individuals or groups to overcome or reduce various pressures that interfere their own life. Lowland rice farmers in Indonesia are dominated by smallholder farmers, with small income. The income that has not been able to meet their needs can put a burden on them, to overcome their burdens they need to do coping mechanisms, there are various forms of coping mechanisms, it can be finding another job or hardly sell their own land, and causes conversion of agricultural land. This research aimed to determine the income structure and expenditure structure of lowland rice farmer’s household at Setianagara Village, in Cibeureum District, Tasikmalaya City, and their coping mechanism as well. The design of this research is quantitative descriptive. The results showed that the farmer’s average income at Setianagara Village in one year are only able to meet around 97% of their average expenditure, for solving these problems, farmers adopted coping mechanisms, by increasing their income, changing consumption patterns, increasing food access, and increasing access to buying food.